The African-American student voice : an analysis of the learning, academic and sociocultural experiences in the public school setting - Harvey, Alta Elaine ([publisher not identified], 2000)
Many voices have expressed the solutions to the dismal future of the African American child. SooHoo (1991) suggests that when children's voices are solicited, it is an empowering process that lends itself to action. The voice of the African American child can contribute to that process. African American children should be given the opportunity to make decisions for themselves; their voices should be heard. This study examines the schooling experiences of six African American students. The nature and meaning of these experiences were explored through in-depth interviews, focus group meetings and participant observations. Two research questions launched this study: 1. How do African Americans who are younger view education and their own experiences within the context of institutionalized learning environments? 2. What issues are voiced by young African Americans regarding the role of education in their lives and the educational changes that would provide them with increased opportunity? I conducted an ethnographic study with African American children to determine their perspective on schooling. This study documented the voices of African American children by using four data collection methods: interviewing, focus groups, observation and document analysis. Meaning was extracted from the data collected through a constant comparative analysis. For this study, because of its emphasis on meaning, I used a purposive sample. I asked these students to be participants in the study because of their particular experiences in schooling. The sample selection of participants in this study consisted of six African American students who attended school at the secondary level. All of the participants were assigned pseudonyms. These students represented members of the public school setting. I selected both male and female African American students. Students were selected from the regular education setting. The findings were derived from inductive analysis of the data. Out of the meaning-making process emerged nine major categories and three major themes as described by the respondents. The nine major categories are teacher/student engagement, student success in school, positive expectations, classroom and school procedures/routines, self-image, restructuring schools, the impact of high stakes testing, a sense of community, and an environment that is conducive for learning.